Kidung Tunjung Biru: Metrum dan Makna yang Terkandung Di Dalamnya - I Wayan Pande Sumardika (Perpustakaan Nasional RI, 2019)
This study uses Kidung Tunjung Biru as object. The problems raised in this study include structure and the meaning of Kidung Tunjung Biru. Theory which was employed in this study is a structural theory and semiotic theory. Methods and techniques used in this study were divided into three phases, (1) the stage of data collection method is used to read assisted with translation techniques, (2) the stage of data analysis used descriptive analysis method, and (3) the stage of presentation of the results of the analysis used informal and formal methods. The results obtained from this study is structure of Kidung Tunjung Biru consisting of: metrum and languages. The meaning contained in Kidung Tunjung Biru, consisting of: flowers in a symbolic;the expression of love; and the concept of kalepasan (unity of God and Human).